Pemberdayaan Siswa Sekolah Dasar sebagai Agent of Change dalam Penerapan Self-Hygiene - Ahmad Yani; Venny Patricia (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this activity is to increase the knowledge and awareness of elementary school students at SDN Cimaung 2 to foster self-hygiene behavior through the habit of cutting nails and brushing teeth regularly. The preliminary survey showed that more than 50% of students still did not get used to clean and healthy behaviors (PHBS), especially in cutting nails and brushing their teeth regularly. This form of community service is carried out through counseling on the benefits of cutting nails and brushing teeth regularly as well as how to cut nails and brush teeth properly, then followed by direct practice. The evaluation results showed an increase in students' knowledge about the benefits of getting used to cutting nails and brushing their teeth regularly and how to do it properly and correctly. Through PHBS activities at school, it is expected that students can increase self-hygiene awareness and be able to become agents of change in a wider community.